Presence of Colletotrichum acutatum and Colletotrichum gloeosporioides on leatherleaf fern, key lime, papaya, star fruit and mango in Costa Rica and Florida (United States) - Barquero Quirós, Marcia (2013)
Anthracnose is a disease caused by several species of the genus Colletotrichum on different hosts. C. acutatum and C. gloeosporioides are 2 morphologically similar species that can cause similar disease symptoms on the same host. A total of 220 isolates of Colletotrichum species were collected from typical anthracnose lesions on leatherleaf fern (Rumohra adiantiformis), Key lime (Citrus aurantifolia), starfruit (Averrhoa carambola), papaya (Carica papaya) and mango (Mangifera indica) in Costa Rica and Florida. Isolates were characterized by colony morphology, benomyl sensitivity and PCR with specific primers for C. acutatum and C. gloeosporioides CaInt2 and Cg/fInt1, respectively. Of the 85 isolates obtained from mango, all 33 isolates from Florida were identified as C. acutatum, whereas all isolates from Costa Rica were C. gloeosporioides. Out of 60 isolates obtained from starfruit, 3 isolates from Costa Rica were C. acutatum (first report) and the rest were C. gloosporioides. All isolates from leatherleaf fern (25 isolates) and Key lime (25 isolates) were identified as C. acutatum. All remaining isolates from startfruit and mango, as well as all isolates from papaya, were C. gloeosporioides. There was no symptom difference between both Colletotrichum species on those hosts were both species were found.